Riverbank Slope Erosion Monitoring Using Unmanned Aerial Vehicle (UAV) - Ngadiman, Norhayati; Mohd Kasan, Nurnafisa; Hamzan, Fikri Hakim; Syed Zakaria, Syed Firdaus (Multidisciplinary Applied Research and Innovation, 2020)
River slope erosion is one of the major and unpredictable dangers worldwide including in Malaysia. Slope erosion is an important geomorphology in influencing changes in the river channels and the development of floodplains. It is a natural process and it could lead to a serious problem if not monitor and maintain properly by the authority. This paper aims to identify and detects factors that contributed to the riverbank slopes erosion. Site surveying was conducted to find a suitable study area and an interview was carried out to gain information regarding the study area. The study area is located at Sungai Kesang, Tangkak Johor with a study area approximately around 90m x 45m with a coordinate of 2’06’21” N and 102’29’17” E. Pilot testing method was applied to create the flight route and to identify the suitable configuration before collecting the data. Based on the results obtained, several types of erosion had been identified such as rainsplash erosion, rill erosion and gully erosion occurred at the riverbank. These types of erosion had been detected in both 3D model: Model 1 and Model 2. The significant factors for each slope erosion were also determined. The findings approved that by using UAV, the images of the slope can be captured and 3D modeling can be developed. Through this method, erosion can be identified from the beginning and the step of the controller can be done immediately.